2021
DOI: 10.1124/jpet.120.000435
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Ro Ameliorates High-Fat Diet–Induced Obesity and Insulin Resistance in Mice via Activation of the G Protein–Coupled Bile Acid Receptor 5 Pathway

Abstract: Obesity, a well-known risk factor in multiple metabolic diseases, is dramatically increasing worldwide. Ginsenosides extracted from ginseng have been reported against obesity and the associated metabolic disorders. As a subtype of ginsenoside, ginsenoside Ro is a critical constituent of ginseng. However, its specific effects on obesity remains unknown. G protein-coupled bile acid receptor 5 (TGR5, also known as GPBAR1) is a bile acid membrane receptor, widely expressed in human tissues contributing to various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Among them, the contents of ginsenoside Ro, chikusetsusaponin Ⅳa, and achyranthoside C in A. bidentata increased significantly after drug pairing. Ginsenoside Ro is an oleanolic acid-type saponin found in A. bidentata, which has been shown to inhibit apoptosis and inflammation of rat chondrocytes by inhibiting the NF-κB signaling pathway [26], and could improve obesity and insulin resistance induced by a high-fat diet in mice by activating Takeda G-protein-coupled receptor 5 (TGR5) [17]. Another study also found that the ginsenoside Ro content increased when used in a combined ginseng decoction with Trogopteroum feces or Raphani semen, suggesting that the combined decoction promoted the dissolution of ginsenoside Ro [27].…”
Section: In Vitro Sample Content Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the contents of ginsenoside Ro, chikusetsusaponin Ⅳa, and achyranthoside C in A. bidentata increased significantly after drug pairing. Ginsenoside Ro is an oleanolic acid-type saponin found in A. bidentata, which has been shown to inhibit apoptosis and inflammation of rat chondrocytes by inhibiting the NF-κB signaling pathway [26], and could improve obesity and insulin resistance induced by a high-fat diet in mice by activating Takeda G-protein-coupled receptor 5 (TGR5) [17]. Another study also found that the ginsenoside Ro content increased when used in a combined ginseng decoction with Trogopteroum feces or Raphani semen, suggesting that the combined decoction promoted the dissolution of ginsenoside Ro [27].…”
Section: In Vitro Sample Content Determinationmentioning
confidence: 99%
“…In this study, 10 representative components were selected through basic research of drug-pair chemicals and a related literature review, including representative compounds with reported pharmacological activity in both E. ulmoides and A. bidentata [17][18][19][20], and unique components of E. ulmoides and A. bidentata with no previously reported quality control (QC) standards. Thus, there is a need to optimize existing methods to develop a suitable method that can detect the above selected components equally sensitive to lower sample concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides is the main active components of ginseng, which regulates glucose and lipid metabolism by inducing gluconeogenesis reduction and glucose transport ( Bai et al, 2018 ). Ginsenoside Ro improves IR by activating TGR5 to promote GLP-1 secretion and energy expenditure in adipose tissue in DIO mice, which suggests that ginsenoside Ro is a potential compound for the treatment of T2DM ( Supplementary Table S1 ) ( Jiang et al, 2021 ). Jyoti et al found that Pregnane-Oximino-Alkyl-Amino-Ether (compound 14b), a TGR5 agonist, improved glucose tolerance in sucrose-loaded rats by increasing glucose utilization in skeletal muscle and hepatocytes ( Supplementary Table S1 ).…”
Section: Other Treatments For Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…In addition, insulin resistance refers to the decreased sensitivity of the body to insulin and is closely related to metabolic syndrome and T2DM. It was reported that ginsenoside Ro ameliorated obesity and insulin resistance induced by high fat diet in mice by activating the TGR5 pathway (Jiang et al, 2021). And ginsenoside Mc1 improved liver steatosis and insulin resistance by reducing endoplasmic reticulum stress (Roh et al, 2020).…”
Section: Recent Findings Of Ginseng In the Treatment Of Vascular Dysf...mentioning
confidence: 99%